Interactions Between Regulatory Variants in CYP7A1 (Cholesterol 7α-Hydroxylase) Promoter and Enhancer Regions Regulate CYP7A1 Expression. (October 2018) - Wang, Danxin; Hartmann, Katherine; Seweryn, Michal; Sadee, Wolfgang
Abstract : Background: CYP7A1 (cholesterol 7α-hydroxylase) catalyzes the rate-limiting step in bile acid biosynthesis from cholesterol—a main pathway for cholesterol removal from the body. CYP7A1 single-nucleotide polymorphisms (SNPs) are associated with total cholesterol and LDL (low-density lipoprotein) levels, risk of cardiovascular diseases, and other phenotypes; however, results are inconsistent, and causative variants remain uncertain, except for a frequent promoter SNP (rs3808607). Methods: We used chromatin conformation capture (4C assay), chromatin immunoprecipitation qPCR assay in hepatocytes, and CRISPR (clustered regularly interspaced short palindromic repeats)-mediated genome editing in hepatocellular carcinoma cell line cells to identify regulatory regions for CYP7A1. We then screened for SNPs located in regulatory regions, testing effects on reporter gene assays and on hepatic CYP7A1 expression by measuring allelic mRNA expression imbalance. Results: 4C assays showed several regions interacting with CYP7A1 promoter. CRISPR-mediated genome editing in hepatocellular carcinoma cell line cells revealed a novel CYP7A1 enhancer and a repressor region, located >10 kb downstream of the CYP7A1 promoter. SNP screening with an allelic mRNA expression imbalance in human livers and reporter gene assays identified a frequent functional SNP (rs9297994) located in the downstream CYP7A1 enhancer region. SNP rs9297994 is in high linkage disequilibrium with promoter SNP rs3808607 but has opposite effects on CYP7A1 mRNA expression. Their combined effects using a 2-SNP model robustly associate with hepatic CYP7A1 mRNA expression, ranging >2 orders of magnitude. Moreover, only the 2-SNP model, but not each SNP alone, is significantly associated with LDL levels, risk of coronary artery disease, statin response, and diabetes mellitus in several clinical cohorts, including CATHGEN (Catheterization Genetics) and Framingham. Conclusions: Two interacting regulatory SNPs modulate CYP7A1 expression and are associated with risk of coronary artery disease and diabetes mellitus. Abstract : Supplemental Digital Content is available in the text.